Rove Beetles of Florida, Staphylinidae (Insecta: Coleoptera: Staphylinidae) - J. Howard Frank; Michael C. Thomas (EDIS)
Revised! EENY115, a 13-page illustrated fact sheet by J. Howard Frank and Michael C. Thomas, is part of the Featured Creatures collection. It introduces the Florida representatives of this large, diverse, and important family of beetles — description, life cycle and habits, and subfamilies in Florida. Includes references. Published by the UF Department of Entomology and Nematology, January 2010.